Lactogenic Hormones Regulation of Glucose Transporters Gene Expression in Lactating Bovine Mammary Epithelial Cells - Zhao, K.; Liu, H.Y.; Zhou, M.M.; Liu, J.X. (Asian Journal of Chemistry, 2011)
The effect of lactogenic hormones (prolactin, insulin and hydrocortisone) on expression of glucose transporters (GLUTs) gene was examined using lactating bovine mammary epithelial cells (BMEC) culture system. Compared with control (no hormone), inclusion of prolactin (10, 100 or 1000 ng/mL) and insulin (5, 50 or 500 ng/mL) did not affect abundance of GLUT1 mRNA (P > 0.05). Prolactin at 100 or 1000 ng/mL down-regulated, whereas insulin at all concentrations up-regulated the expression of GLUT8 mRNA (P < 0.05), indicating that GLUT8 may be responsive to insulin in bovine mammary epithelial cell. The abundance of GLUT1 and GLUT8 mRNA increased by hydrocortisone at 10 ng/mL, but decreased when treated at higher level (100 or 1000 ng/mL). Interaction of hydrocortisone and insulin on GLUT8 gene expression was observed (P = 0.002) and hydrocortisone counteracted the insulin-stimulated expression of GLUT8 mRNA. When three hormones were added together at their physiological concentrations during lactation (100 ng/mL prolactin, 5 ng/mL insulin and 100 ng/mL hydrocortisone), the expression of GLUT1 and GLUT8 mRNA was depressed (P < 0.05), similar to the result with 100 ng/mL of hydrocortisone. It is inferred that lactogenic hormones may not be involved in the regulation of abruptly increased expression of GLUT1 and GLUT8 mRNA in bovine mammary gland during the early lactation and hydrocortisone may play the major role in the regulation of GLUT1 and GLUT8 gene expression.